1997
DOI: 10.1523/jneurosci.17-06-02101.1997
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins Suppress Apoptosis Induced by Deafferentation of an Avian Motor-Cortical Region

Abstract: Studies of the developing nervous system led to the general view that growth factors promote neuronal survival in a "retrograde" manner. For example, release of NGF from postsynaptic peripheral targets followed by uptake and retrograde transport by presynaptic neurons provided a widely accepted conceptual framework for the action of neurotrophins. In contrast, although presynaptic or "anterograde" influences on the survival of developing neurons have been recognized for some time, the mechanisms by which affer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 60 publications
5
87
0
Order By: Relevance
“…A more remote, but possible, source of IGF-II peptide in HVC could be the mMAN neurons that project into HVC. This type of orthograde transport has been observed for IGF-I in the olivary -cerebellar system (Nieto-Bona et al, 1993) and for BDN F and N T3 in songbirds (Johnson et al, 1997). Whatever the source, the presence of IGF-II in H VC could protect a subset of RA-projecting cells from cell death while others die and are replaced.…”
Section: Functional Implications Of Igf-ii In Hvcsupporting
confidence: 55%
See 1 more Smart Citation
“…A more remote, but possible, source of IGF-II peptide in HVC could be the mMAN neurons that project into HVC. This type of orthograde transport has been observed for IGF-I in the olivary -cerebellar system (Nieto-Bona et al, 1993) and for BDN F and N T3 in songbirds (Johnson et al, 1997). Whatever the source, the presence of IGF-II in H VC could protect a subset of RA-projecting cells from cell death while others die and are replaced.…”
Section: Functional Implications Of Igf-ii In Hvcsupporting
confidence: 55%
“…In addition, many of these trophic factors also play a role in the maintenance of the adult nervous system (for review, see Lo, 1995;Thoenen, 1995). Recently, it has been shown that BDNF and NT3 promote the survival of neurons in the developing song system (Johnson et al, 1997).…”
mentioning
confidence: 99%
“…In that case, the density of BDNF immunoreactivity was also comparable in the surrounding caudal neostriatum (Johnson et al, 2000). Infusing the protein can prevent neuronal death due to deafferentation in juvenile zebra finches (Johnson et al, 1997), suggesting that it might normally facilitate the increased cell survival in males compared to females. In parallel, we found more trkB-containing cells in the song control nuclei of male than female zebra finches at 30 -60 days of age (Wade, 2000).…”
Section: Summary and Future Directionsmentioning
confidence: 78%
“…TrkB mRNA has also been reported in the HVC, RA, and lMAN of 20 -35-day-old individuals of both sexes (Dittrich et al, 1999). It is clear that BDNF exists in song control nuclei and can be transported among them in an anterograde, and probably retrograde, fashion (Dittrich et al, 1999;Johnson et al, 1997), although the data on its pattern of expression are a bit confusing. In situ hybridization has revealed mRNA in HVC specifically at 30 -35 days of age in males but not females (Dittrich et al, 1999), and cells ventral to HVC at 20 days of age.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…We do not know whether BDNF protein produced during previous days contributed to the basal level seen in our nonsinging birds. Finally, and perhaps most importantly, it is known that much of the BDNF protein produced in one site can be carried away by anterograde transport (47,48). If part of the BDNF protein produced in HVC was transported to RA or Area X, then the amount left in HVC would grossly underestimate the amount produced.…”
Section: Discussionmentioning
confidence: 99%